A Pendulum-Based Strategic Supply Chain Alignment Model Incorporating PESTEL Factors and System Adaptation Mechanisms - R. Beniadi Setiawan (Syntax Corporation, 2026)
An increasingly dynamic business environment requires companies to adaptively adjust their supply chain management strategies. Static strategic approaches are often unable to respond to external shocks such as regulatory changes, economic volatility, and technological advancements. Therefore, a conceptual framework is needed to explain the dynamics of continuous strategic alignment. This study aims to develop and operationalize the Pendulum Alignment Theory (PAT) as a dynamic approach to understanding the strategic orientation of the supply chain, which oscillates between cost efficiency, quality, and responsiveness. The method used is a mixed-methods research design that integrates conceptual model development, empirical indicator analysis based on the PESTEL framework, and scenario simulations to evaluate the system’s response to various environmental shocks and managerial interventions. The results indicate that political, legal, and economic factors act as the primary triggers for rapid strategic change, while social and technological factors influence the system’s adaptation speed. Furthermore, environmental demands increase the need for control mechanisms to maintain stability. This study also identifies the importance of trigger thresholds, capability flexibility, and damping management as key strategies in maintaining system equilibrium. In conclusion, PAT offers a theoretical and practical framework capable of explaining and guiding the dynamic alignment of supply chain strategies, thereby helping organizations enhance resilience and performance amid environmental uncertainty.